Varying numbers of players in small-sided soccer games modifies action opportunities during training - Vilar, L.; Esteves, P.; Travassos, B.; Passos, P.; Lago-Peñas, C.; Davids, K. (International Journal of Sports Science and Coaching, 2014)
This study examined the effects of the numbers of players involved in small-sided team games (underloading and overloading) on opportunities for maintaining ball possession, shooting at goal and passing to teammates during training. These practice constraint manipulations were assumed to alter values of key performance variables identified in previous research, such as interpersonal distances between players and time to intercept shots and passes. Fifteen male soccer players (age: 19.60±1.99 years) were grouped into three teams and played against each other in different versions of small-sided soccer games, in which the number of players was manipulated in three different conditions: 5 vs. 5, 5 vs. 4 and 5 vs. 3. Dependent variables were the values of interpersonal distance between an outfield attacker and nearest defender (ID), and the relative distance of a defender needed to intercept the trajectory of a shot (RDishot) or pass (RDipass). Statistical analyses revealed that mean ID values were significantly lower in 5 vs. 5 than in 5 vs. 4 and 5 vs. 3 conditions, and significantly lower in 5 vs. 4 than 5 vs. 3. They also revealed that mean values of RDishot were significantly higher in 5 vs. 3 than in 5 vs. 5 conditions. Finally, results showed that the mean values of RDipass were significantly higher in 5 vs. 3 than in 5 vs. 5. Findings revealed how task constraints in SSGs can be manipulated to vary values of key spatial and temporal performance variables (interpersonal distance and time to intercept) to influence the nature of interpersonal interactions between competing players during practice. We observed that these manipulations tended to decrease opportunities for maintaining ball possession during training when equal numbers of attackers and defenders existed in SSGs, and led to more shots and passes emerging when the number of defenders was decreased relative to attackers.